INTERVENSI NEGARA KETIGA DAN PERAN INDONESIA BERSAMA ASEAN PADA PENYELESAIAN ISU LAUT CINA SELATAN (LCS) - Muhammad Danang Prawira Hutama (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2019)
This paper discusses the development of the issue of the South China Sea (SCS), which until now it is still unclear the direction of its resolution, and over time finally got intervention from a third country, such as the United States (US) through Freedom of Navigation Operations (FONOPS). This is certainly received strong opposition from China that the US action has violated the SCS boundary which is claimed as China's sovereign territory. Indonesia as an ASEAN member country together with other ASEAN countries that claim SCS (Philippines, Vietnam, Malaysia, Brunei Darussalam) is also working to resolve the SCS problem which is still in the process of discussion and signing of the draft SCS Code of Conduct (CoC) with China.